2017
DOI: 10.7448/ias.20.1.21708
|View full text |Cite
|
Sign up to set email alerts
|

Acute HIV infection detection and immediate treatment estimated to reduce transmission by 89% among men who have sex with men in Bangkok

Abstract: Introduction: Antiretroviral treatment (ART) reduces HIV transmission. Despite increased ART coverage, incidence remains high among men who have sex with men (MSM) in many places. Acute HIV infection (AHI) is characterized by high viral replication and increased infectiousness. We estimated the feasible reduction in transmission by targeting MSM with AHI for early ART.Methods: We recruited a cohort of 88 MSM with AHI in Bangkok, Thailand, who initiated ART immediately. A risk calculator based on viral load and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 61 publications
1
40
0
Order By: Relevance
“…While HIV incidence was calculated among clients receiving more than one test during the pilot period and whose repeat testing behaviour may have been prompted by higher levels of risk than single testers, this finding points to a high level of HIV transmission among clients already engaged with a HIV prevention service. While the short follow‐up period and relatively small number of incident cases detected and missing variable data (discussed further below) precluded analysis of factors prospectively associated with HIV acquisition risk, other findings suggest that undiagnosed HIV in the context of infrequent testing and ongoing sexual risk behaviours may be a key contributor to ongoing transmissions . While a lack of CD4 testing at HIV diagnosis in Myanmar prevents an assessment of time spent undiagnosed, the significant association between reporting no HIV testing history and baseline visit HIV positivity implies that some MSM and TW may have spent substantial time with unknown HIV.…”
Section: Discussionmentioning
confidence: 99%
“…While HIV incidence was calculated among clients receiving more than one test during the pilot period and whose repeat testing behaviour may have been prompted by higher levels of risk than single testers, this finding points to a high level of HIV transmission among clients already engaged with a HIV prevention service. While the short follow‐up period and relatively small number of incident cases detected and missing variable data (discussed further below) precluded analysis of factors prospectively associated with HIV acquisition risk, other findings suggest that undiagnosed HIV in the context of infrequent testing and ongoing sexual risk behaviours may be a key contributor to ongoing transmissions . While a lack of CD4 testing at HIV diagnosis in Myanmar prevents an assessment of time spent undiagnosed, the significant association between reporting no HIV testing history and baseline visit HIV positivity implies that some MSM and TW may have spent substantial time with unknown HIV.…”
Section: Discussionmentioning
confidence: 99%
“…However, focusing on reducing the time between tests may come at the expense of testing others for the first time. Testing people more often with the result of identifying more new infections may result in fewer PLHIV being identified as such infections are relatively rare, but as they may be in the acute phase of infection their viral load might be higher and the transmission risk higher [24,25]. Data on community viral load among testers at Mildmay could facilitate prior-itization of groups for testing.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis in Thailand suggested that early diagnosis and treatment during AHI among men who have sex with men could avert 89% of all new infections in this population. 25 Approaches that differentiate service delivery to better address the preferences and needs of unserved and underserved individuals have been identified as a priority to close outstanding gaps in access to HIV prevention and treatment. 26 In implementing differentiated services, it is increasingly clear that a focus on individuals and networks with the greatest viral burdens has strategic benefit.…”
Section: Introductionmentioning
confidence: 99%